“The Best of Both Worlds”. Conceptualising an Urban Sámi Identity - Gjerpe, Kajsa Kemi (Universitetet i Tromsø, 2013)
Indigeneity is often expected to merely exist in rural settings. The urban context is, therefore, considered atypical and inauthentic. I will distinguish between cultural traits and emblems, arguing that the creation of emblems has been an important aspect of revitalisation of Sámi culture. In addition, I maintain that the use of emblems in daily life is important for urban Sámi, as Sámi culture is not very visible in the city environment. However, the use of emblems has had unfavourable consequences. On the one hand, urban Sámi do not belong within the category of ‘ordinary urban citizen’ as they hold cultural traits that are not common in the urban and Norwegian context; nor do they belong within the ‘Sámi’ category as they lack certain expected cultural traits within the rural and Sámi context. Those who fall between the various categories become, arguably, people out of place. Opposing the notion of being of out place, this study seeks to demonstrate how the concept of an urban Sámi identity is created, articulated and challenged in an urban context. I argue that the interviewees belong in both ‘worlds’, and that the city creates a context to various means of cultural expressions.